E-Readiness Competencies of MSU-Naawan Professors and Students' Perceptions on Online Classes amidst COVID-19 - Fernan Q. Abragan (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
The purpose of this study was to identify the professors' e-readiness competencies in implementing online classes in terms of course design, course communication, time management, and technical competence. Also, it aimed to determine the students' perception towards the online class in terms of instructional design and delivery on students, teacher roles on students, and class organization and format. Pure descriptive analysis was used in analyzing the data, such as mean and percentage distribution. Both adapted and adopted survey questionnaires were used to address this research's problem, and these were distributed to the respondents either via online and phone call. Results showed that the senior high school department professors were good enough to use online platforms with an overall mean of 1.76, which implies that most of them are technically sound. Students have agreed that their professors are satisfied with instructional design and delivery, teacher roles, and class organization and format. The overall mean of 3.60 of students' perception towards online class implies that students have perceived their teacher's teaching way amidst pandemics is still promoting students' desire to learn, which engaged them to become more interactive in various activities. Because there are observable few numbers that can be seen in the results indicating that the teachers are not proficient enough in digital literacy, it is highly recommended to get the respondents' demographic profile in terms of age and training attended about computer literacy. It is also recommended that the professors' e-readiness be correlated to students' perception of the online class.